Drawing Gender Equality: A Participatory Action Research Project with Educators in Northern Uganda - Shelley Jones (Engaged Scholar Journal, 2019)
This paper reports upon an arts-based participatory action research project conducted with a cohort of 30 teachers in rural Northwest Uganda during a one-week professional development course. Multimodality (Kress & Jewitt, 2003; Kress & van Leeuwen, 2001) was employed as a “domain of inquiry” (Kress, 2011) for social semiotics (meaning-making within a social context) within which the participants both represented gender inequality as well as imagined gender equality. Multimodality recognizes the vast communicative potential of the human body and values multiple materials resources (such as images, sounds, and gestures) as “organized sets of semiotic resources for meaningmaking” (Jewitt, 2008, p. 246). Providing individuals with communicative modes other than just spoken and written language offers opportunities to include voices that are often not heard in formal contexts dominated by particular kinds of language, as well as opportunities to consider topics of inquiry from different perspectives and imagine alternative futures (Kendrick & Jones, 2008). Findings from this study show how a multimodal approach to communication, using drawing in addition to spoken and written language, established a democratic space of communication. The sharing and building of knowledge between the participants (educators in local contexts) and facilitator (university instructor/researcher) reflected a foundational tenet of engaged scholarship which requires “…not only communication to  public audiences, but also collaboration with communities in the production of knowledge” (Barker, 2004, p. 126).